Modern weapons and military equipment for issue 1-2017 - Ostojić, Nikola M. (Vojnotehnički glasnik / Military Technical Courier, 2016)
The exercises of Russian and Serbian pilots BARS 2016 and 2016 Slovenian brotherhood Members of our armed forces, especially the Air Force, from the experienced Russian pilots, learn new lessons about the use of modern aircraft. The development of military equipment in the world, weapons and other techniques require a new understanding of the country’s defense and the lag can be prevented modernization of our armed forces, as well as practicing members of the Army of Serbia in the new tactical procedures and preparing for possible new forms of opposition to aggression. With international cooperation and gaining new experiences our army trained for participation in multinational military forces. Exercise Serbian and Russian pilots BARS 2016, established itself as the main task after the purchase of two planes MIG-29 and helicopters MI-17. Not only does the introduction of annual and combat characteristics of these aircraft, but also to master the tactical use in complex combat. There is no doubt that the Russian pilots have very valuable experience in interdiction operations with the aircraft MIG-29, as well as in an air battle. This aircraft has exceptional flight possibilities and under the skillful hand pilot can perform very complex maneuvers that provide supremacy in the airspace and the victory in the air battle. Therefore, the exercise of Russian and Serbian pilots BARS 2016 can be seen, as a significant progress in mastering basic modern combat actions in securing their own airspace, control and countering the aggressive actions of possible opponents. In addition, this was an excellent opportunity for our members of the Air Force are trained to rescue downed pilots. Exercise „Slovenian brotherhood 2016”, which followed a joint pilot practicing Russia and Serbia, contributed to the military-tactical training of Serbian Army for efficient operation in the anti-terrorist struggle. For this exercise involved members of the Russian and Belarusian special forces, as well as a special aircraft IL-76, which are designed to transport paratroopers and assault operations in the zone of operations. Also, from this aircraft desanted is an armored personnel vehicle. Exercise has been given the motto "Determined Response Three Army", given the fact that it represents a common response of special anti-terrorist unit of the three brotherly countries in the functioning of the armed terrorist forces. Exercises with Russian and Belarusian members, our army is trained for successful participation in multinational operations, which is more in the overall quality of training the armed forces of our country.